Spallation Neutron Production in the Dubna Transmutation Assembly - Zamani, M.; Fragopoulou, M.; Manolopoulou, M.; Stoulos, S.; Debeauvais, M.; Brandt, R.; Westmeier, W.; Krivopustov, M.; Sosnin, A. (HNPS Advances in Nuclear Physics, 2019)
A large lead target with a U blanket was irradiated by 1.5 GeV protons at the Dubna Nuclotron accelerator. Spatial distributions of neutron fluxes were determined by Solid State Nuclear Track Detectors in the new experimental transmutation assembly. Slow and fast neutron components were studied inside sections of the setup and on the U blanket surface. Neutron distributions after Cd and polyethylene shielding were also investigated. The results show that the new arrangement is efficient mainly to transmutation experiments by fission and (η,χη) reactions as well as by (η,γ) reactions.